PEMBINAAN AKHLAK SANTRI MELALUI PEMBELAJARAN KITAB TA’LIM AL-MUTA’ALLIM DI PONDOK PESANTREN AL-MUTTAQIN KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Marhamah, Marhamah (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2021)
Among the motivations of parents to put their children into boarding schools is to get children who have good morals and virtuous, and it is proven by the difference in manners of the generation of boarding school graduates with graduates of other educational institutions in the middle of public life. In this case an interesting aspect to see is the peculiarity of learning resources and learning methods that exist in boarding schools so as to give birth to a generation that has noble morals. Therefore, this research aims to reveal the development of morality in boarding schools through the study of the book of Ta'lim al-Muta'allim. This research uses qualitative approach, the data source used is ustaz, santri and document analysis in the form of Ta'lim al-Muta'allim. Techniques for collecting observation data, interviews and documentation studies. The research data was analyzed with a qualitative approach. The results prove that the content of Ta'lim al-Muta'allim directs everyone who learns it to have noble morals. The method used by teachers in teaching morality through the book of Ta'lim al-Muta'allim is more dominated by the method of civility.